2010
DOI: 10.1111/j.1466-7657.2010.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcultural nursing concept: a study of nursing students in Turkey

Abstract: The majority of students experience cultural diversity in patient care. It is thought that transcultural care placed in curriculum even as a separate course will guide nursing students in all stages of patient care. Thus, the effect of cultural diversity in patient care can be minimized with the help of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 17 publications
1
31
0
3
Order By: Relevance
“…It is reported in a study that Izmir and Gaziantep were among the provinces that received the highest rate of immigration . In similar studies made in our country with nursing and/or midwifery students, the rates of caregiving of individuals from different cultures of students were found to be 69.4, 68.8 and 85.5% . Similarly, Sargent et al .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…It is reported in a study that Izmir and Gaziantep were among the provinces that received the highest rate of immigration . In similar studies made in our country with nursing and/or midwifery students, the rates of caregiving of individuals from different cultures of students were found to be 69.4, 68.8 and 85.5% . Similarly, Sargent et al .…”
Section: Discussionsupporting
confidence: 71%
“…Ayaz et al . found that the issues where cultural differences were experienced to the highest degree were differences in dialect and pronunciation (53.4%), and differences of language (37%) among nursing students . Similarly, Tortumluoglu et al .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations